Beneficial Effect of Long-Term Administration of Supplement With Trapa Bispinosa Roxb. and Lutein on Retinal Neurovascular Coupling in Type 2 Diabetic Mice - Hanaguri, Junya; Yokota, Harumasa; Kushiyama, Akifumi; Kushiyama, Sakura; Watanabe, Masahisa; Yamagami, Satoru; Nagaoka, Taiji (Frontiers in Physiology, 2022)
Purpose: We investigated the effect of long-term administration of supplement with trapa bispinosa roxb.extract (TBE) and lutein on the susceptibility of retinal blood flow regulation in type 2 diabetic mice. Methods: Six-week-old db/db mice were randomly divided into the untreated group (n = 6) and the treated group received the supplement with TBE and lutein (n = 6). The longitudinal changes in retinal blood flow responses to systemic hyperoxia and a flicker stimulation were evaluated every 2 weeks in diabetes db/db mice from age 8 to 14 weeks. The retinal blood flow was assessed using laser speckle flowgraphy. We also evaluated the expressions of glial fibrillary acid protein (GFAP) and vascular endothelial growth factor (VEGF) by immunofluorescence. Results: The resting retinal blood flow was steady and comparable between two groups throughout the study. In db/db mice with supplement, both blood flow responses were restored from 8 to 14 weeks of age compared with diabetic mice treated with the placebo. Supplement prevented the activation of GFAP and decreased the expression of VEGF detected by immunofluorescence compared with the diabetic mice treated with placebo. Conclusions: We found that the long-term administration of supplement with TBE and lutein improved the impaired regulation of retinal blood flow in response to systemic hyperoxia and flicker stimulation, suggesting that these supplements can prevent diabetic retinopathy by improving abnormal neurovascular coupling in type 2 diabetic mice.